Drug shortages in Israel: regulatory perspectives, challenges and solutions - Eyal Schwartzberg; Denize Ainbinder; Alla Vishkauzan; Ronni Gamzu (BMC, 2017)
Abstract Background Pharmaceutical drug shortages (DSs) are a global problem which presents challenges to countries around the world. Shortages of pharmaceutical products may have a direct detrimental impact on public health and patients' wellbeing by causing delayed, or even lack of, treatment. Moreover, DSs may force both patients and caregivers to use unfamiliar drugs, which could lead to medication errors. The objective of our study was to analyze DSs in Israel during the years 2013-2015, assessing their etiology and exploring the steps taken for their mitigation and prevention. Methods The database of the Israeli Ministry of Health (MoH) on drug shortages contains all the DSs recorded in Israel since 2013, detailing the cause of the DS, its duration, steps taken in its' management and the availability of generic or therapeutic alternatives. Selected examples of DSs from the database are described in this paper in order to identify the causes of DSs, the scope of the problem and possible solutions. Additionally, we have reviewed the recent activities performed by European Medicine Agency (EMA) and the American Food and Drug Administration (FDA) in their efforts to minimize this problem. Results Several factors contributing towards DSs in Israel were identified, including quality problems in both the final drug product and in the raw materials, upgrades and improvements of the manufacturing process required by the MoH, manufacturing by a sole supplier, dramatic price decrease in off-patent medications causing the manufacturer to discontinue the distribution of the product in Israel, just-in-time inventory control, and others. One of the most important steps in managing drug shortages was identified to be early notification of the shortage by the Marketing Authorization Holder (MAH) to the MoH. In 2013, the Israeli MoH updated the regulation on drug shortages instructing MAHs on their obligation of early notification to the MoH. Furthermore, various steps dealing with marketing withdrawal of drugs and temporary drug shortages are being implemented in Israel, such as suspending any further reductions in drug prices below 17 new Israeli shekels, instructing all MAHs to maintain no less than 1 month supply of all registered and non-registered drugs in Israel and allowing an expedited registration pathway for well-established use/grandfather drugs. Conclusions Drug shortages pose significant public health hazards worldwide. Early notification to the MoH and open dialog with MAHs are essential for managing DSs and mitigating their impact. Despite the efforts carried out by health regulatory authorities worldwide, DSs still pose a significant threat to public health.